Cryo‐EM structure of orphan G protein‐coupled receptor GPR21 - Thian‐Sze Wong; Wei Gao; Geng Chen; Chen Qiu; Guodong He; Fang Ye; Zhangsong Wu; Zicheng Zeng; Yang Du (MedComm, 2023)
Abstract GPR21 belongs to class A orphan G protein‐coupled receptor (GPCR). The endogenous ligands for human GPR21 remain unidentified. GPR21 expression is associated with developing type 2 diabetes (T2DM), a multifactorial metabolic disease caused by pancreatic β‐cell dysfunction, decreasing insulin production, insulin resistance, and obesity. Animal studies suggested that GPR21 is a potential therapeutic target for T2DM treatment. The underlying mechanisms leading to GPR21 self‐activation remain unknown. In our co‐expression analysis, we noted that GPR21 could also form a stable complex with an unreported Gα protein subtype, Gαs. To gain further insights into the structural mechanisms of GPR21 activation, we employed cryo‐electron microscopy (cryo‐EM) and single‐particle analysis to resolve the high‐resolution structure of GPR21‐Gαs complexes. The clear electron density map of the GPR21‐Gαs provided direct evidence that GPR21 could couple to Gαs protein at physiological conditions. Thus, GPR21 might mediate previously unexplored pathways in normal or pathological conditions, which warrants further investigation. Structure‐guided mutagenesis and biochemical analysis revealed that extracellular loop 2 (ECL2) of GPR21 is essential for the receptor transducing intracellular signal via cAMP. Together, the new structure data reveal a novel signaling cascade of human GPR21 mediated by ECL2 and provide fundamental information for future structure‐based drug development.